Determination of iodide in potassium iodide dosage tablets using cathodic stripping voltammetry with a carbon paste electrode - Švancara, Ivan; Vytřas, Karel (Univerzita Pardubice, 2002)
A method for the determination of iodide in potassium iodide-containing pharmaceutical formulas is presented. Special attention has been paid to the effect of thiosulphate used as the stabiliser of solid iodide. The procedure utilising a tricresyl phosphate-containing carbon paste electrode in combination with cathodic stripping voltammetry has been applied to the analysis of real samples of iodide tablets.
Keywords: stanovení; jodidy; stripping voltametrie; uhlíkové pastové elektrody